198k views
5 votes
Which is the solution to 2x - y = 1

4x + y = 11.

A (2, 3)

B (3, 2)

C ( -2, 3)

D (3, -2).

I RLLY need an explanation.

2 Answers

7 votes

Answer A.

Step-by-step explanation:

{2x - y = 1

{4x + y = 11 (+)

---------------------------------

2x + 4x - y + y = 1 + 11

6x = 12 | : 6

x = 2

{x = 2

{2 ยท 2 - y = 1

{x = 2

{4 - y = 1 | + y

{x = 2

{4 = 1 + y | - 1

{x = 2

{y = 3

User Alqueraf
by
6.6k points
4 votes

Answer:

A (2, 3)

Step-by-step explanation:

2x - y = 1

4x + y = 11.

By adding both equation we got :

6x = 12

x = 12/6 = 2

Put value of x in first equation

2x - y = 1

2(2) - y = 1

4 - y = 1

y = 4-1 = 3

Points are (2,3)

User Bob Ebert
by
5.7k points